The role of social communities in empowering communities through the transformation of waste into marketable products - Syafmaini, Iis Elfa; Zulharman; Rismawati (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Waste is a global issue that requires serious and sustainable handling. Waste management problems are not only the responsibility of the government or related institutions, but also a shared duty of society — including social communities. Methods: This research uses a qualitative method with a descriptive approach. Data collection techniques include primary sources — namely, social community administrators — and secondary sources such as necessary documentation. Data was collected through observation, interviews, and documentation from websites and social media accounts of several community organizations. The data analysis technique involved data reduction, data presentation, and drawing conclusions. Findings: The results of the study show that community empowerment programs have been successfully implemented, including educational initiatives such as seminars, training sessions, and city-wide clean-up campaigns, as well as the establishment of waste banks and social media awareness campaigns. The waste management methods applied by these communities include bata terawang, loseda, biopores, composting buckets, and maggot-based processing. During the implementation of these empowerment efforts, several challenges emerged, such as inadequate facilities, low public awareness of proper waste management practices, and limited financial resources in the early stages of the communities' formation. Conclusion: It can be concluded that the role of social communities in empowering the public through waste management has made a real contribution to reducing and transforming waste into valuable materials. Novelty/Originality of this article: Social communities empower people using an andragogical approach — an educational method that treats adult learners as peers. These communities have succeeded in empowering society through various channels of life, such as direct education, social media outreach, and by setting real-life examples of proper waste management.